Student Behavior Intention: An Analysis of Culture, Lecturer Performance, and Academic Services Quality - Weny Putri; Feby Astrid Kesaulya; Yohanes Dicka Pratama (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
This study aims to determine the influence of student's culture, lecturer's performance, and academic service quality based on student perception on behavior intention of Musi Charitas Catholic University students (UKMC). The analysis used path analysis with the Structural Equation Model (SEM). The results showed that cultural variables, lecturer performance, and academic service quality from student perceptions influenced the intention of UKMC students to behave. The results of this study provide information related to student culture, academic services that students want, and the ability of lecturers from the student's point of view as well as how these variables affect their intention to behave. This information can provide a gap for UKMC to be able to make improvements in some aspects that are still felt less than customer needs perceptions. Customer needs fulfillment is ultimately expected to shape the positive behavior of UKMC students.